Framing Mining Response of User Interaction According to User’s Demand in Diverse Spatial Data Cloud - Haseeb Ahmad, Mohd; Kumar Gupta, Bineet (International Journal of Computer Sciences and Engineering, 2025)
Although we witness routine computer based implementations on daily basis for utilization in real life, still we are further more distanced from better abstractions from spatial data. This paper introduces a framework to mine spatial data that provide better handling of user requirements on real time spatial data. The frameworks use two tier software paradigm which is vital for better mining strategies.